Case report: A rare cause of intestinal perforation in a third-trimester pregnant woman - Stiegler, Clemens; Kapitza, Christopher; Weber, Florian; Patalakh, Wladimir; Schäfer, Claus (Frontiers in Medicine, 2024)
Background An acute abdomen is a medical emergency that requires early diagnosis and treatment. In pregnancy, this process is significantly more challenging, and radiological findings are sometimes unclear due to the enlarged uterus displacing other structures. Moreover, endometriosis-related complications are rare, and the disease is often undiagnosed. Case presentation We report a case of acute perforation of the cecum and appendix during pregnancy (35 weeks of gestation) caused by a previously unknown, deep infiltrating endometriosis with focal ulceration of the affected bowel wall, which sonographically seemed to be acute appendicitis. Conclusion Despite the relatively low risk, clinicians should be aware of possible endometriosis-associated complications in pregnancy with potentially life-threatening events, even in previously unknown endometriosis. Further studies should evaluate intestinal complications during pregnancy in relation to previous treatment of intestinal endometriosis (conservative vs. surgical).